The Effectiveness of Android-Based ESMED on Decreasing Cholesterol Value and Blood Pressure among Risk of Chronic Heart Disease Patients - Fatimah - Zahra; Kusnanto Kusnanto; Padoli Padoli (International Journal of Nursing and Health Services (IJNHS), 2020)
Coronary heart disease (CHD) is a leading cause of death and disability worldwide. This study used a quantitative method with a quasi-experimental design with a pre-post control group study approach. The study was conducted at the Puskesmas in Malang district. The inclusion criteria, such as patients with aged 25-50 years old, be able to operate an Android-based mobile with API 4.0. Data were analyzed using the Non-Parametric Wilcoxon Rank test. There was an increase in respondents in the risk category for mild CHD in the control and treatment groups. There was a significant effect of the application of Android-based ESMED applications on decreasing the total cholesterol and systolic blood pressure. There is still a cholesterol value of respondents at 200 mg/dl in the control group and treatment. The results of the systolic blood pressure among the control group and the treatment group showed that the range of systolic blood pressure from ??140-149 mmHg before and after receiving the intervention. The Android-based ESMED (Early Screening, Monitoring, and Education) application effectively reduces cholesterol and blood pressure in patients at risk for CHD.